FRACTIONAL VAN DER POL EQUATION BY ADOMIAN DECOMPOSITION METHOD - Othman, Sumayah Ghaleb; Yahya Qaid Hasan (IJRDO -JOURNAL OF MATHEMATICS, 2020)
Adomian Decomposition Method (ADM) is successfully used to find the approximate solution of fractional Van der Pol equation. The ADM can be used to solve the ordinary, partial and fractinal differential equations. In this work, we will study fractional Van der Pol equation by (ADM). The numerical resultes of y(x) for the considered fractional Van der Pol equation is obtained.